Down Syndrome Screening Using Nuchal Translucency Thickness and Nasal Bone Eximination of Fetus at Maternal Age >= 35 Yearss. - Ilham Oetama Marsis (Fakultas Kedokteran Universitas Kristen Indonesia, 2007)
Abstract The aim of this study is so evaluate a non-invasive method to screen for Down syndrome. We measured nuchal translucency thickness (NT) using a fixed cut-off of ³’3d3.0 mm with a crown-rumph lenght (CRL) of 50-70 mm and nassal bone (NB) examination at 11—13+6 weeks of gestation. The study was conducted from January 2001 to January 2004. NT was measured at 11-13+6 weeks of gestation and NB was examined from January 2002 to January 2004. Case with NT of at least 3.0 mm were submitted for toxoplasma, rubella cytomegalovirus, and herpes simplex virus I and II (TORCH) examination. Genetic amniocentesis was performed at 16 weeks of gestation. Both antenatal and postnatal management were carried out. NT was measured in 175 cases between January 2001 and January 2002. Combined NT measurement and NB examination were performed in 215 cases between January 2002 and January 2004. Maternal age ranged from 35 – 43 years with first to fifth gravidity. Seven out of 175 NT cases, had NT of at least 3.0 mm. The detection rate (DR) was 71.4% (5/7) and the false-positive rate (FPR) was 1.2% (2/170). Of the 215 NT plus NB absence cases, eight had an NT ofat least 3.0 mm and seven had no NB. The combination of maternal age, NT and NB examination give a DR of 87.5%% (7/8 paralleled to 7/7) and FPR of 0.48% (1/208). Screning can be performed in the clinical setting by measuring NT and NB examination at 11-13+6 weeks of gestation. Key word: Down syndrome, nuchal translucency, nasal bone, ultrasonography. Abstrak Penelitian ini bertujuan untuk menilai penggunaan metode non invasif untuk penapisan sindrom down. Diukur nuchal translucency thickness (NT) dengan cut-of ³’3d3.0 mm, crown-rumph length (CRL) 50-70 mm dan pemeriksaan tulang hdung (nasal bone-NB) pada umur kehamilan 11-13+6 minggu. Penelitian dilakukan sejak Januari 2001 sampai dengan Januari 2004. NT diperiksa pada umur kehamilan 11-13+6 minggu dan NB diperiksa Janari 2002 sampai Januai 2004. Pada kasus dengan NT 3.0 mm atau lebih dilakukan pemeriksaan TORCH. Amniosentesis untuk pemeriksaan genetik dilakukan pada minggu ke-16 kehamilan. Selain itu, juga dilaksanakan pemeriksaan dan penanganan antenatal dan postnatal. NT dinilai pada 175 kasus antara Januari 2001 dan Januari 2002. Kombinasi pengukuran NT dan NB dilakukan pada 215 kasus antara Januari 2002 dan Januari 2004. Umur ibu hamil berkisaran antara 35-43 tahun dengan variasi kehamilan pertama sampai kelima. Tujuh dari 175 kasus NT mempunyai ukuran 3,0 mm atau lebih. Angka deteksi pemeriksaan (DR) tersebut adalah 71,4% (5/7) dan angka positif palsu (FPR) 1,2% (2/170). Pada 215 kasus NT dan NB, delapan mempunyai ukuran NT 3,0 mm atau lebih dan tujuh tanpa NB. Kombinasi umur ibu dan pemeriksaan NT dan NB memberikan angka DR 87,5%% (7/8) paralel terhadap 7/7) dan FPR 0,48% (1/208). Penapisan dapat dilakukan di klinik dengan mengukur NT dan NB pada minggu 11-13+6 kehamilan. Kata Kunci : Sindroma Down, translusensi nukhal, tulang nasalis, ultrasonografi